Phylogenetic trees and other evolutionary diagrams in biology textbooks and their importance in secondary science education - Machová, Markéta (Scientia in educatione, 2021)
Diagrams describing relationship between organisms, and their overall evolution, commonly in the form of phylogenetic trees or other evolutionary diagrams, have become a part of even lower secondary biology textbooks. These diagrams can help promote basic science literacy, yet their design may also strengthen misconceptions about evolution. Therefore, based on the content analysis of 112 Czech biology textbooks for secondary schools (ISCED levels 2 and 3), characteristics of introduced phylogenetic trees and other evolutionary diagrams were recorded and evaluated according to the cladistics to see if their construction supports the current scientific understanding of evolution. The content analysis indicates that the design of nearly half of all diagrams in current lower (ISCED 2) and upper secondary (ISCED 3) textbooks promotes ladder thinking. More than 80% of all diagrams were not accompanied by instructions on how to read them, meaning that students did not have sufficient scaffolding to understand them. Mainly ISCED 3 textbooks did not introduce additional problem tasks that would support the use of the diagrams in the lessons. Therefore, authors of textbooks should focus more on the construction quality of these diagrams while also supporting their correct application during the educational process. This is likely to prevent a further increase in student misconceptions.